Analytical investigation of nonlinear heave-coupled response of tension leg platform. (August 2019) - Tabeshpour, Mohammad Reza; Hedayatpour, Reza
Having deep view in structural response of tension leg platform is important issue not only for response analysis but also for engineering design. Coupling between surge and heave motions of tension leg platform is such a problem. Here, tension leg platform motions are considered only in surge and heave degrees of freedom without pitch effect. The coupled term of heave is a nonlinear differential equation. Because the focus of this article is on this term, therefore, Duffing equation of motion in the surge direction is linearized. The wave forces are calculated using Airy's wave theory and Morison's equation, ignoring the diffraction effects. Current force also can be very important in dynamic analysis of tension leg platform. Because it affects the term of heave that is coupled with surge. It is shown that the effect of surge motion coupling on heave motion is very important in large displacement of surge motion in many sea states. The main result is that the coupling effects appeared in some frequencies such as heave and surge frequency, twice the frequency of wave, twice the natural surge frequency, and summation and difference of frequency of wave and surge frequency.